2015
DOI: 10.1021/ja511680u
|View full text |Cite
|
Sign up to set email alerts
|

Stability and Kinetics of c-MYC Promoter G-Quadruplexes Studied by Single-Molecule Manipulation

Abstract: A DNA G-quadruplex (G4) formed at the oncogene c-MYC promoter region functions as a gene silencer. Due to its high stability at physiological K(+) concentrations, its thermodynamics and kinetic properties have not been characterized in physiological solution conditions. In this work, we investigated the unfolding and folding transitions of single c-MYC G4 and several of its truncated or point mutants at 100 mM KCl concentration under mechanical force. We found that the wild type could fold into multiple specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
95
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(103 citation statements)
references
References 32 publications
7
95
0
1
Order By: Relevance
“…The G4 forming ssDNA sequences were ligated with 5′-thiol labeled 489 bp and 5′-biotin labeled 601 bp dsDNA prepared by polymerase chain reaction as described previously (6,32). The ligated products were purified by gel extraction with PureLink kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The G4 forming ssDNA sequences were ligated with 5′-thiol labeled 489 bp and 5′-biotin labeled 601 bp dsDNA prepared by polymerase chain reaction as described previously (6,32). The ligated products were purified by gel extraction with PureLink kit (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that G4 structures exist in vivo (3,4) where they are involved in multiple biological processes including DNA replication, transcription, translation and telomere maintenance (2). Due to their high thermal and kinetic stability, G4 structures often present a physical barrier to various processes taking place on DNA and RNA (5,6). In vivo , the G4 barrier is overcome by a set of helicases that can unfold G4 structures (710).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent designs allow simultaneous and independent application of forces and torques (13,14), and one report (15) describes a way to decouple twist fluctuations from applied forces. Other developments include a portable version (16), a design with sub-nanometer extension precision (17), a magnetic system for steering beads (18,19), integration of a very high speed camera (20), magnetic micro-manipulation of confined DNA (21), and use of proteins (instead of DNA) as tethers (22). …”
mentioning
confidence: 99%
“…achieved many remarkable results in the field of DNA nano-assembly, which might be applied to potential gene carriers, drug delivery systems, and gene-silencing therapy and cellular imaging3293031. By contrast, evidence has previously showed that the guanine-rich sequence of the c-myc promoter forms G-quadruplex structures because of three or four guanine bases that are associated in a cyclic array via Hoogsteen hydrogen bonding arrangements3233. Studies in our laboratory showed that ruthenium (II) complexes can also facilitate stability of the c-myc G-quadruplex DNA3435.…”
mentioning
confidence: 99%